The long march : a reform agenda for Latin America and the Caribbean in the next decade by Shahid Javed Burki and Guillermo E. Perry.. - Burki, Shahid Javed. (World Bank Latin American and Caribbean studies, 1997)
"Detailed discussion of reforms necessary to accelerate economic growth and reduce poverty in the region. Reforms include equity market development, civil service reform, in health and education investment, labor market liberalization, and greater trade openness"--Handbook of Latin American Studies, v. 57.